2017
DOI: 10.1186/s12864-017-4312-3
|View full text |Cite
|
Sign up to set email alerts
|

Weighted likelihood inference of genomic autozygosity patterns in dense genotype data

Abstract: BackgroundGenomic regions of autozygosity (ROA) arise when an individual is homozygous for haplotypes inherited identical-by-descent from ancestors shared by both parents. Over the past decade, they have gained importance for understanding evolutionary history and the genetic basis of complex diseases and traits. However, methods to infer ROA in dense genotype data have not evolved in step with advances in genome technology that now enable us to rapidly create large high-resolution genotype datasets, limiting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 250 publications
0
8
2
Order By: Relevance
“…Moreover, the proportion of individuals with runs of homozygosity of intermediate length is negatively correlated (correlation coefficient = −0.26, p -value = 1.02 < 10 −3 ) with log 10 (BF) (Table S2), likely due to the narrower genomic signature left behind by soft sweeps relative to hard sweeps. In contrast, we observe no significant correlation for smaller runs of homozygosity (classes 2 and 3), which have also been proposed to potentially be affected by selective sweeps [Pemberton et al, 2012, Blant et al, 2017].…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…Moreover, the proportion of individuals with runs of homozygosity of intermediate length is negatively correlated (correlation coefficient = −0.26, p -value = 1.02 < 10 −3 ) with log 10 (BF) (Table S2), likely due to the narrower genomic signature left behind by soft sweeps relative to hard sweeps. In contrast, we observe no significant correlation for smaller runs of homozygosity (classes 2 and 3), which have also been proposed to potentially be affected by selective sweeps [Pemberton et al, 2012, Blant et al, 2017].…”
Section: Resultscontrasting
confidence: 84%
“…We further explored the existence of a more general relationship between top sweep candidates and the prevalence and length of runs of homozygosity. Previous research has indicated that short-to-intermediate runs of homozygosity spanning tens to hundreds of kilobases are characteristic of recent sweeps [Pemberton et al, 2012, Blant et al, 2017], and we sought to examine whether there was a correlation of G123 or sweep softness (using log 10 (BF) as proxy) with the proportion of individuals falling in a run of homozygosity of specific length. To this end, we intersected our top candidates lists with the inferred coordinates of short to intermediate runs of homozygosity from Blant et al [2017].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the proportion of individuals with runs of homozygosity of intermediate length is negatively correlated (correlation coefficient = 20.26, P-value = 1:02 3 10 23 ) with log 10 ðBFÞ (Table S2), likely due to the narrower genomic signature left behind by soft sweeps relative to hard sweeps. In contrast, we observe no significant correlation for smaller runs of homozygosity (classes 2 and 3), which have also been proposed to potentially be affected by selective sweeps (Pemberton et al 2012;Blant et al 2017).…”
Section: Analysis Of Empirical Data For Signatures Of Sweepscontrasting
confidence: 84%
“…Previous research has indicated that short-to-intermediate runs of homozygosity spanning tens to hundreds of kilobases are characteristic of recent sweeps (Pemberton et al 2012;Blant et al 2017), and we sought to examine whether there was a correlation of G123 or sweep softness [using log 10 ðBFÞ as proxy] with the proportion of individuals falling in a run of homozygosity of specific length. To this end, we intersected our top candidates lists with the inferred coordinates of short to intermediate runs of homozygosity from Blant et al (2017). We found that the proportion of individuals with runs of homozygosity of intermediate length (class 4) is positively correlated (correlation coefficient = 0.32, P-value = 3:66 3 10 25 ) with G123 (Table S2), likely due to stronger and more recent sweeps generating larger G123.…”
Section: Analysis Of Empirical Data For Signatures Of Sweepsmentioning
confidence: 99%